Gender as a variable of individual speech in linguistics (Kurdish language “Sorani dialect” for example) - Hassan, Asst.L.Sakar Abdullah; Khader, Asst.L.Ghafoor Arif (Sulaimani Journal for Humanities, 2026)
From a sociolinguistics perspective, gender is not just a biological division between male and female, but is seen as a “social variable” that directly affects language choices and speech patterns. While “gender” refers to physical differences, it is a cultural and social concept that describes the roles and identities that society assigns to its individuals.Language is not a neutral tool, but a mirror to reflect the position of power and social relationships. In this context, gender speech differences are interpreted as the result of the socialization process, ie individuals learn how to express their gender identity through language. This paper investigates the phenomenon of “gender speech differences” in the discourse structure of Kurdish society from a sociolinguistic perspective within the framework of sociolinguistic theories. The main problem of this research revolves around the extent to which “gender identity as a “social variable” affects linguistic form and content. The research focuses on living examples of Kurdish language at the levels of phonetics, lexicography, and semantics The most important findings of the study indicate that linguistic differences do not only reflect biological differences, but also reflect “social status” and “gender roles” in Kurdish culture Male speech moves towards the directness and functionality of language. The study concludes that language is a major tool for building social identity and consolidating gender differences in Kurdish society
Keywords: Social gender; Kurdish language; gender representation